Genome-Wide Identification of Genes Related to Biosynthesis of Phenolic Acid Derivatives in Bletilla striata at Different Suspension Culture Stages - Liu, Houbo; Huang, Ceyin; Li, Qingqing; Wang, Mufei; Xiao, Shiji; Shi, Junhua; He, Yihuai; Wen, Weie; Li, Lin; Xu, Delin (Frontiers in Plant Science, 2022)
To screen the genes regulating the biosynthesis of phenolic acid derivatives from the genome of Bletilla striata, we designed a suspension culture system to sample the cells for the following experiments. The contents of four phenolic acid derivatives were determined by high-performance liquid chromatography, and several full-length transcriptome sequencings of RNA samples at 10 time points were performed for bioinformatics analysis. The correlation analysis was used to identify and verify the key DEGs involved in the biosynthesis of the four phenolic acid derivatives. The results showed that the contents of p-hydroxybenzylalcohol (HBA), Dactylorhin A, Militarine, and Coelonin peaked at 33 days postinoculation (Dpi), 18 Dpi, 39 Dpi, and 39 Dpi of the culture system, respectively. Based on transcriptome data, 80 DEGs involved in the biosynthesis of phenolic acid derivatives were obtained. The KEGG pathway enrichment analysis classified them mostly into five metabolic pathways: phenylpropane biosynthesis, starch and sucrose metabolic, cyanoamino acid metabolism, gluconeogenesis and glycolysis, and phenylalanine metabolism. qPCR analysis revealed that the relative gene expression levels were consistent with the overall trend of transcriptome sequencing results. Among them, 14, 18, 23, and 41 unigenes were found to be involved in the synthesis of HBA, Dactylorhin A, Coelonin, and Militarine, respectively. These unigenes laid a solid foundation for elucidating the biosynthesis mechanism of phenolic acid derivatives in suspension cells of B. striata.